2022
DOI: 10.3390/ijerph19084845
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Intradural Hematoma after Spinal Anesthesia in a Young Male Patient: Case Report and Review of the Literature

Abstract: Spinal intradural hematoma (SIH) is a rare condition which can cause neurological sequelae such as permanent motor weakness and sensory loss in the lower extremities. Herein, we describe a case of SIH following spinal anesthesia. The patient was a 30-year-old man who underwent treatment for accessory navicular syndrome at our department. The patient was not receiving anticoagulation therapy, and spinal anesthesia was thus selected. No symptoms of hematoma were observed in the immediate postoperative period, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, Rettenmaier et al 9 argue that superior results with conservative management in SSDHs reflect a selection bias as only patients who have severe deficits are offered surgery, while those who are preserved neurologically are usually managed with medications. Conversely, Ji et al 4 state that there is a 63.6% chance of developing permanent deficits and sphincter loss in those who have neurological symptoms but do not undergo surgery as opposed to such poor outcomes in only 17.9% in cases with symptoms who undergo surgery and advocate intervention as soon as possible as was done in this instance.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, Rettenmaier et al 9 argue that superior results with conservative management in SSDHs reflect a selection bias as only patients who have severe deficits are offered surgery, while those who are preserved neurologically are usually managed with medications. Conversely, Ji et al 4 state that there is a 63.6% chance of developing permanent deficits and sphincter loss in those who have neurological symptoms but do not undergo surgery as opposed to such poor outcomes in only 17.9% in cases with symptoms who undergo surgery and advocate intervention as soon as possible as was done in this instance.…”
Section: Discussionmentioning
confidence: 95%
“…They also state that among all spinal hematomas caused by LPs epidural hematoma is the commonest (75%), while subarachnoid hematoma and SSDH account for 15.7 and 4.1%, respectively. 4 Kreppel et al 5 too reported only 25 cases (4%) of SSDHs in a meta-analysis of 613 patients of spinal hematomas with varying etiologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have examined spinal intradural hematomas as a result of trauma, iatrogenic causes, spinal anesthesia, or coagulopathy, though the exact etiology for these hemorrhages can remain unknown in a nontrivial percentage of cases. 1,[5][6][7][8][9] Furthermore, the distribution of hematoma location follows a relatively bimodal distribution, clustering in the cervical spine and the lower thoracic spine. 1 To our knowledge, an example of cervical intradural hematoma associated with traumatic nerve root avulsion has not been published since 1980.…”
mentioning
confidence: 99%